Breaking barriers: Harnessing project-based learning to empower students with learning disabilities - Bong, Lie Chien; Kong, Vestly Liang Soon; Kuppusamy, Suresh Kumar (Jurnal Pendidikan Bitara UPSI, 2025)
This study examines the effectiveness of Project-Based Learning (PBL) as an instructional approach for students with learning disabilities (LD). It focuses on how PBL promotes autonomy, collaboration, critical thinking, and problem-solving skills among students with diverse learning needs. Using a qualitative research approach, the study reviews existing literature on PBL and learning disabilities, as well as case studies from four schools that implemented PBL strategies. The case studies involved a period of 8 weeks, with interviews conducted with 10 educators and analysis of student portfolios to understand the practical application of PBL in inclusive classrooms. The study highlights the significant impact of PBL on student engagement and motivation. PBL helps students with LD by fostering a more dynamic learning experience compared to traditional passive learning environments. It promotes critical thinking, enhances collaboration, and supports self-regulation. The integration of assistive technologies, such as speech-to-text applications, proved crucial in supporting students’ cognitive development and keeping them motivated. Challenges identified include cognitive overload, executive function difficulties, and the need for individualized support. The study discusses how these challenges can be mitigated through differentiated instruction, clear scaffolding, and appropriate use of assistive technologies. The paper concludes that PBL can empower students with LD when thoughtfully structured and supported with the right tools. Practical implications for educators include the need for professional development in PBL strategies, the integration of assistive technology, and the importance of providing tailored support structures for students.